Hydrogen Sulfide Alleviates Skeletal Muscle Fibrosis via Attenuating Inflammation and Oxidative Stress - Zhao, Linlin (Front Physiol, 2020)
The purpose of this study was to investigate the effect of exogenous hydrogen sulfide (H(2)S) treatment on skeletal muscle contusion. We established a skeletal muscle contusion model (S group) and an H(2)S treated of skeletal muscle contusion model (H(2)S group). Gastrocnemius muscles (GMs) were collected at day 1, day 5, day 10, and day 15 after injury, and comprehensive morphological and genetic analyses was conducted. H(2)S treatment reduced M1 macrophage (CD68), profibrotic cytokines (TGF-β), pro-inflammatory cytokines (TNF-α, IFN-γ, IL-1β, and IL-6), chemokines (CCL2, CCR2, CCL3, CCL5, CXCL12, and CXCR4), matrix metalloproteinases (MMP-1, MMP-2, MMP-9, and MMP-14) and oxidative stress factor (gp91phox) expression levels, improved M2 macrophage (CD206) level. Thus, exogenous H(2)S treatment reduced inflammation and oxidative stress, attenuated skeletal muscle fibrosis, and partly improved skeletal muscle injury.